If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4p + 11 + -1(-5p) + -2 = 0 Remove parenthesis around (-5p) -4p + 11 + -1 * -5p + -2 = 0 Multiply -1 * -5 -4p + 11 + 5p + -2 = 0 Reorder the terms: 11 + -2 + -4p + 5p = 0 Combine like terms: 11 + -2 = 9 9 + -4p + 5p = 0 Combine like terms: -4p + 5p = 1p 9 + 1p = 0 Solving 9 + 1p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 1p = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 1p = 0 + -9 1p = 0 + -9 Combine like terms: 0 + -9 = -9 1p = -9 Divide each side by '1'. p = -9 Simplifying p = -9
| 36x^2-36x-216=0 | | 400+50x=4000 | | -81=-4+7(6b-5) | | y+4=0.5x+1 | | -7y+12+2y-1= | | 6(x+3)-8x=36 | | 4(8k+5)= | | (3x-5)(2x+8)= | | (x+3)(x+3)=X^2+81 | | 456=(20+2x)(15+2x) | | 1+4(x-8)=4-5(x-1) | | x^2+y^2-6x+4y+6=0 | | 8n+14=2n-4 | | 9x+3y=167 | | 5(5+x)+10=5-5x | | 3x-10+x+14=160 | | 2x-1+6=11 | | 7y^2+4y= | | 6m+4(6m-4)=26-8(2m-12) | | 3x+6y=168 | | 2(x+7)-5(2x-6)=92 | | 12x^2+4x=-5 | | p+4p=15 | | 1=-16x^2+b | | 9x+6y=171 | | 4cos^2(x)=5-4sinx | | 9x+6y=170 | | x*20=2 | | 18=-16t^2+80t+18 | | log(4x+1)=log(25) | | (cozx-1)(cosx-2)=0 | | 3x^2+24x+3=0 |